1994
DOI: 10.2307/3870008
|View full text |Cite
|
Sign up to set email alerts
|

Nar-1 and Nar-2, Two Loci Required for Mla 12 -Specified Race-Specific Resistance to Powdery Mildew in Barley

Abstract: Previously isolated susceptible host mutants were used in a genetic and functional study of the resistance response of barley specified by resistance gene Mla12 to the fungal pathogen Erysiphe graminis f sp hordei. Mutant M66 represents a defective allele of Mla12, whereas M22, M82, and M100 represent mutations in loci unlinked to Mla12. Intermutant crosses of the latter three show that susceptibility in M82 and M100 is caused by allelic, recessive mutations that define the Nar-1 gene (necessary for Mla12 resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 0 publications
2
38
0
2
Order By: Relevance
“…Mutations at the Rarl and Rar2 loci (originally named Narl and Nar2) significantly compromised Mlamediated resistance and caused reduced HR formation and defense-gene induction (Freialdenhoven et al, 1994). However, mutant rar alleles do not affect Mlg-mediated resistance (J. Jorgensen and P. Schulze-Lefert, unpublished data).…”
Section: Tobacco N Gene-mediated Resistance To Tmvmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations at the Rarl and Rar2 loci (originally named Narl and Nar2) significantly compromised Mlamediated resistance and caused reduced HR formation and defense-gene induction (Freialdenhoven et al, 1994). However, mutant rar alleles do not affect Mlg-mediated resistance (J. Jorgensen and P. Schulze-Lefert, unpublished data).…”
Section: Tobacco N Gene-mediated Resistance To Tmvmentioning
confidence: 99%
“…Quantitative cytological investigations indicate that putative R gene-mediated host cell defense responses can occur at several distinct stages of fungal ontogeny, depending on the R locus involved. Mla allele-mediated resistance involves predominantly the HR of cells containing haustoria, and the induction of numerous defense-related genes (Freialdenhoven et al, 1994;Boyd et al, 1995). Mlg allele-mediated resistance acts earlier and involves papillae formation ( Figure 1C); the HR occurs to0 late to be considered causal to fungal arrest (Gorg et al, 1993).…”
Section: Tobacco N Gene-mediated Resistance To Tmvmentioning
confidence: 99%
“…Large surveys for mutants in loci necessary for normal R gene function have been undertaken (Freialdenhoven et al, 1994(Freialdenhoven et al, , 1996. Using such a genetic approach, Salmeron et al (1996) identified a gene, Prf, necessary for Pto function.…”
Section: How Is the Hr Induced?mentioning
confidence: 99%
“…In barley, gene interaction studies have shown that a mutant allele of a gene required for Mla-based resistance (rar1; Freialdenhoven et al, 1994) does not abolish Mlgbased resistance at the macroscopic level. Interestingly, at the microscopic level, the rar1 mutation modifies the Mlg resistance phenotype.…”
Section: How Is the Hr Induced?mentioning
confidence: 99%
“…The hypersensitive reaction (HR) of plants to avirulent pathogens restricts pathogen growth effectively and includes a characteristic PCD of one or a few cells at the site of pathogen invasion (6)(7)(8)(9). Interestingly, although plant BI-1 expression can inhibit BAX-induced PCD in yeast and Arabidopsis, overexpression of Arabidopsis BI-1 in resistant RPM1 plants appeared not to interfere directly with the hypersensitive cell death reaction induced by avirulent Pseudomonas syringae pv.…”
mentioning
confidence: 99%